Pengaruh Belajar Tuntas Dan Motivasi BelajarTerhadap Hasil Belajar Ips Siswa Kelas VSD Negeri Kadipiro 2 Sambirejo SragenTahun Pelajaran 2015/2016 - Danung, Tri Ananta; , Drs.Rubino Rubiyanto, M.Pd (2016)
The purpose of this study was to determine 1) the effect of mastery learning on learning outcomes of V class social students at SD N Kadipiro 2. 2) the effect of the motivation learning the learning outcomes of V class social e students at SD N Kadipiro 2. 3) the influence of mastery learning and learning motivation to the learning outcomes of social sciece in grade V in SD N Kadipiro 2. This research is a quantitative research. This study took place in SD N Kadipiro 2. The population in this study were students of V class In SD N Kadipiro 2 taken as a sample of 33 students. The technique of taking the side by using sample population.The technique of collecting data using questionnaires and documentation techniques. Data analysis technique used is multiple linear regression analysis. The conclusion of this study are 1) mastery learning positive and significant impact on learning outcomes of the IPS on the V class students of SD N Kadipiro 2. Based on t test obtained t> t table, namely 2,697 > 2,045 and the significance value <0.05 is 0.005 <0.05. learning motivation and significant positive effect on the learning outcomes of the IPS on the V class students of SD N Kadipiro 2. Based on t test obtained t> t table, namely yaitu 2,494 > 2,045 and the significance value <0.05 is 0.010 <0.05. Mastery learning and learning motivation together positive and significant impact on learning outcomes of the IPS on the V class students of SD N Kadipiro 2. Based on F test obtained Fhitung 5,59 > Ftabel 2,93, with a probability value 0.000 <0.05. Mastery learning variables contribute effectively 15,35%. Variable learning motivation contribute effectively to 21,42%. By comparing the value of the effective contribution appears that learning motivation has a more dominant influence on learning achievement than the variable of mastery learning.